2004
DOI: 10.5194/hess-8-751-2004
|View full text |Cite
|
Sign up to set email alerts
|

Towards reduced uncertainty in catchment nitrogen modelling: quantifying the effect of field observation uncertainty on model calibration

Abstract: The value of nitrogen (N) field measurements for the calibration of parameters of the INCA nitrogen in catchment model is explored and quantified. A virtual catchment was designed by running INCA with a known set of parameters, and field measurements were selected from the model run output. Then, using these measurements and the Shuffled Complex Evolution Metropolis algorithm (SCEM-UA), four of the INCA model parameters describing N transformations in the soil were optimised, while the measurement uncertainty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…For example, Futter et al (2014) implemented a Monte Carlo-based approach for sensitivity and parameter uncertainty analysis of the PERSiST model for River Thames, finding that the model results were especially sensitive to evapotranspiration parameters and residence times. The uncertainty of the INCA model has been assessed in several papers, such as for example Raat et al (2004), who pointed out the problem of equifinality and suggested a multi-objective calibration approach, as well as the use of frequent measurements (fortnightly frequency) as reference values for calibration. Dean et al (2009) applied a generalised likelihood uncertainty estimation (GLUE) framework to the INCA-P model, and concluded that the uncertainty due to the model structure and parameterisation was similar to the uncertainty of the measured values of total phosphorus in the river.…”
Section: Impacts On Phytoplankton Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Futter et al (2014) implemented a Monte Carlo-based approach for sensitivity and parameter uncertainty analysis of the PERSiST model for River Thames, finding that the model results were especially sensitive to evapotranspiration parameters and residence times. The uncertainty of the INCA model has been assessed in several papers, such as for example Raat et al (2004), who pointed out the problem of equifinality and suggested a multi-objective calibration approach, as well as the use of frequent measurements (fortnightly frequency) as reference values for calibration. Dean et al (2009) applied a generalised likelihood uncertainty estimation (GLUE) framework to the INCA-P model, and concluded that the uncertainty due to the model structure and parameterisation was similar to the uncertainty of the measured values of total phosphorus in the river.…”
Section: Impacts On Phytoplankton Concentrationmentioning
confidence: 99%
“…However, it can be assessed qualitatively. This modelling combination involves around 20-25 influential parameters, based on previous uncertainty assessments on the models used in this study (Dean et al, 2009;Futter et al, 2014;Raat et al, 2004;Rankinen et al, 2006;Whitehead et al, 2015b). However, as stated for example by Skeffington et al (2007), translating input uncertainties into uncertainty in the outputs is typically less than the summed uncertainty in the input parameters.…”
Section: Impacts On Phytoplankton Concentrationmentioning
confidence: 99%
“…On the other hand, the complexity of deterministic models often creates intensive data and calibration requirements, which generally limits their application in large watersheds. Deterministic models also lack robust measures of uncertainty in model coefficients and predictions, although recent developments for hydrological applications can be used in biogeochemical models as well (Raat et al, 2004). Nonetheless, deterministic models are abstractions of reality that can include unrealistic assumptions in their formulation.…”
Section: R Marcé and J Armengol: Modeling Nutrient In-stream Processesmentioning
confidence: 99%
“…Mechanistic models often lack robust measures of uncertainty in model coefficients and predictions, although recent developments for hydrological applications can also be used in biogeochemical models (Raat et al, 2004). Uncertainty analysis of more simple approaches such as the nutrient spiraling concept is much less difficult (Marcé and Armengol, 2009).…”
Section: A Recipe For Integrated Modelingmentioning
confidence: 99%